The Uyghur lobby : global networks, coalitions, and strategies of the World Uyghur Congress - Chen, Youwen (New York : Routledge, 2014)
'The Uyghur Lobby is the first systematic and contemporary examination of the global operations of the World Uyghur Congress (WUC). The Uyghur lobby is not a unified movement; wide divisions exist regarding how activists should promote national self-determination. The localization of the movement leads its affiliate organizations to find their own paths for survival. Framing of the Uyghur issue plays a vital role in allowing local Uyghur affiliate to create independent alliances and bases of support. In general, people who tend to involve themselves with WUC member organizations share a belief that the cause of Uyghur self-determination can only be achieved through peaceful means, and in that context, the protection of human rights in China is a prime concern. In discussing the Uyghur lobby in the US, Germany and Japan, it becomes clear that most of the coalitions cobbled together in the domestic political arena are a reflection of the political games within these countries. The Uyghur lobby is thus highly constrained by the broader domestic politics of its host countries to have actual policy impacts to realize its political ambition.This unique and timely study reveals how an issue concerning a Chinese minority has been catapulted onto the wider global political stage, and how Uyghur groups have been successful in raising their visibility. As such, it will be of great interest to students and scholars working on Chinese politics, the Uyghur issue, and minority and ethnic politics, social movements, human rights, and international politics more broadly.'--
Includes bibliographical references and index.
Keywords: Uighur (Turkic people) -- Politics and government; Uighur (Turkic people) -- Ethnic identity; Uighur (Turkic people) -- Government relations; Xinjiang Uygur Zizhiqu (China) -- Politics and government; Xinjiang Uygur Zizhiqu (China) -- Ethnic relations; Xinjiang Uygur Zizhiqu (China) -- Social conditions